Numerical Study on Heat Transfer and Release Characteristics of Key Components in Electrically Heated Tobacco Products - Bo Zhang; Lingjun Xiao; Jiejie Huang; Zhiguo Wang; Naiping Gao; Wen Du; Bo Kong; Zhiwei Sun; Ping Huang; Jianxin Ren; Bin Li; Yihan Gao (International Journal of Chemical Engineering)
Electrically heated tobacco products (EHTPs) could release effective aerosol components from tobacco materials at relatively low temperatures without a burning phenomenon. It is essential to grasp the temperature distribution and release mechanism of key components in heated tobacco materials. The existing experimental studies have provided initial insights into the thermodynamic behavior of tobacco materials under various conditions. However, current numerical models are still in their early stages of development, with the majority failing to correlate heat transfer with component release. Based on this, a coupled numerical model of gas flow, heat transfer, and the release of key components in the electrically heated tobacco product is established in this study, which exhibits improvements in revealing the internal heat and mass transfer characteristics in the porous media of tobacco and is capable of evaluating the influence of component contents and product design parameters. The release rates of water, glycerol, and nicotine components are quantitatively described by the first-order Arrhenius formula, and the transport of heat and gas flow is simulated using the Navier-Stokes equation. The accuracy of the model is validated through experiments, including temperature monitoring at multiple measurement points and determination of residual contents in the tobacco substrate after each puff. The simulation results suggest that an appropriate component ratio and tobacco filler mass can enhance both the release amount and release efficiency of key components, and reducing either the diameter or length of the tobacco section can help to improve the heat transfer performance. A slower heating rate matched with longer preheating times enables the complementary release of water and glycerol components, which helps to regulate the uniformity of component content in the aerosol to some extent. This study helps to provide suggestions for the design and optimization of electrically heated tobacco products.